Assessment of silica aerogel/nano-TiO2 (AG/TiO2) composite material and its application in photocatalytic coating. Issue 5 (4th May 2021) - Liu, Lele; Zhao, Piqi; Wang, Shoude; Xie, Ning; Wang, Han; Strokova, Valeria; Lu, Lingchao; Cheng, Xin
ABSTRACT: How to give a full play of the photocatalytic performance of TiO2 in coatings has attracted immense academic interests in recent years. A major challenge is the good dispersion, more reactivity area and cost-effective fabrication. Here, TiO2 -silica aerogel composite (AG/TiO2 ) was achieved in one step by silane coupling reaction. And the absorbance test proved that the bonding between them possessed satisfactory mechanical stability. SEM-EDS and BET analysis showed TiO2 could be well dispersed on the surface of AG clusters until it reached the maximum load amount approximate 6 wt%, which was in accordance with the regularity of photocatalytic performance. In the case of the optimum, the RhB degradation rate of AG/TiO2 could reach 82% by UV irradiation for 4 h. Subsequently, AG/TiO2 was mixed with polyacrylate emulsion to prepare photocatalytic functional coating. During the film formation process, the AG/TiO2 particles were supposed to migrate up spontaneously, which was proved by semi-quantitative XPS analysis of Si-dispersion. It would undoubtedly improve the rate of effective utilization of TiO2 in coatings. And the photocatalytic efficiency of RhB could be up to 88% at a low percentage (6%) after 8 h UV illumination. Furthermore, we also proved that the gradient-dispersed AG/TiO2 did not impair the mechanical properties of PAE coating. GRAPHICAL ABSTRACT: uf0001